Characterization of patients with clinical suspicion of dengue and warning signs. Pediatric Hospital. Cienfuegos, 2019 - Delfín Rodríguez Buergo; Hilda María Delgado Acosta; Diana Rosa Rodríguez Delgado; Roxana Gutiérrez Morán; Lisset María Martínez González (Medisur)
Background: The endemic-epidemic behavior of dengue in Cienfuegos has shown an increasing incidence every year in the child population, with an increase in the report of warning signs. The correct hospital approach to these cases, to avoiding fatal outcomes, is of great importance for the maternal and child area. Objective: to characterize patients with clinical suspicion of dengue and who developed warning signs. Methods: a descriptive study was carried out, which included 41 patients admitted to the Intensive Care Unit of the Cienfuegos Pediatric Hospital in 2019. The variables analyzed were: sex, age, nutritional status and associated chronic diseases, time between admission and beginning of symptoms, warning signs of the disease, reflection in the clinical history of the home and / or study center environment epidemiological situation, hospital stay and clinical evolution. Results: female sex and preschool ages predominated, as well as normal weight (95.1%). 26.8% suffered from chronic diseases. Patients admitted more than 48 hours after the beginning of symptoms predominated. The most frequent warning signs were thrombocytopenia, fluid in the cavity (pleural, pericardial and perivesicular), vomiting and abdominal pain. The evolution was favorable. Conclusion: The identified alarm signs indicate that the patients in the series could have evolved towards the severe stage of the disease, however, thanks to the early detection of the signs and the care received, the evolution was favorable.